Anomalous right coronary artery arising next to the left coronary ostium: unambiguous detection of the anatomy by computed tomography and evaluation of functional significance by cardiovascular magnetic resonance - Korosoglou, Grigorios; Heye, Tobias; Giannitsis, Evangelos; Hosch, Waldemar P.; Kauczor, Hans-Ulrich; Katus, Hugo (International journal of cardiology, 2010)
Herein we report on the diagnostic potential of multi-detector row computed tomography (MDCT) combined with cardiovascular magnetic resonance (CMR) for the diagnostic workup in an adult patient with a rare coronary anomaly. MDCT unambiguously detected the anomalous right coronary artery (RCA), which originated next to the left coronary ostium and coursed inter-arterially between the ascending aorta and the pulmonary trunk. The intramural proximal intussusception of the ectopic RCA could be clearly appreciated on MDCT images, while multiple mixed plaques were detected in the left anterior descending (LAD), resulting in moderate stenosis of this vessel. CMR during adenosine infusion ruled-out inducible ischemia, yielding normal perfusion patterns both in the RCA and in the LAD coronary territory. Since ischemia was not demonstrated by stress CMR, revascularization was not performed.
Online veröffentlicht am 25. Januar 2009
Gesehen am 22.03.2023